2021
DOI: 10.1039/d1ra02605d
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic evolution model of coal permeability during enhanced coalbed methane recovery by N2 injection: experimental observations and numerical simulation

Abstract: A dynamic evolution model of coal permeability during CH4 displacement by N2 injection was proposed, considering the combined effects of matrix swelling/shrinkage and effective stress, for providing a reference on N2-ECBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“… 2 , 3 CBM extraction can not only reduce the risk of gas outburst but also yield clean energy and improve the efficiency of energy utilization. 4 , 5 The average CBM extraction concentration in China is lower than 20 and 80% of the air entering the drainage system under a low negative pressure. 6 , 7 There are two ways to increase the CBM extraction concentration: (1) to address problems, such as small pore size and massive adsorption in low-permeability coal seams, by means of hydraulic fracturing, hydraulic cutting, and coal seam water injection 8 11 and (2) to improve the sealing effect through narrowing down the gas leakage channels of boreholes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 3 CBM extraction can not only reduce the risk of gas outburst but also yield clean energy and improve the efficiency of energy utilization. 4 , 5 The average CBM extraction concentration in China is lower than 20 and 80% of the air entering the drainage system under a low negative pressure. 6 , 7 There are two ways to increase the CBM extraction concentration: (1) to address problems, such as small pore size and massive adsorption in low-permeability coal seams, by means of hydraulic fracturing, hydraulic cutting, and coal seam water injection 8 11 and (2) to improve the sealing effect through narrowing down the gas leakage channels of boreholes.…”
Section: Introductionmentioning
confidence: 99%
“…Coalbed methane (CBM) is a kind of unconventional natural gas mainly adsorbed to coal seams and their surrounding rock . As its pressure and concentration increase considerably, CBM has become one of the main hazards in coal mines. , CBM extraction can not only reduce the risk of gas outburst but also yield clean energy and improve the efficiency of energy utilization. , The average CBM extraction concentration in China is lower than 20 and 80% of the air entering the drainage system under a low negative pressure. , There are two ways to increase the CBM extraction concentration: (1) to address problems, such as small pore size and massive adsorption in low-permeability coal seams, by means of hydraulic fracturing, hydraulic cutting, and coal seam water injection and (2) to improve the sealing effect through narrowing down the gas leakage channels of boreholes. The former has been widely used, whereas the latter still has a long way to go with respect to the sealing material. Both sides of the roadway undergo yield deformation due to concentrated stress.…”
Section: Introductionmentioning
confidence: 99%
“…), low permeability is one of the main characteristics of coal seams in China. To rely on the original permeability of coal seams for gas extraction is far from solving the problem of coal-mine gas-disaster prevention and best utilization of energy resources. In order to improve the efficiency of gas extraction, measures for transforming the structure of coal deposits by boosting cracks that penetrate the coal seam are the most commonly used means to increase the permeability. , To this end, a variety of technologies for enhancing the permeability of low-permeability coal seams have been carried out by many researchers, including hydraulic techniques, deep-hole explosive blasting, dense drilling, liquid nitrogen freeze-thaw, fluidized mining, protective-layer mining, and the acidification technique. These methods have had some success in increasing the permeability of low-permeability coal seams but have limitations. , In order to realize an efficient extraction of CBM, it is still necessary to actively explore and put forward new technology for improving the permeability of low-permeability coal deposits.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the efficiency of gas extraction, measures for transforming the structure of coal deposits by boosting cracks that penetrate the coal seam are the most commonly used means to increase the permeability. 8,9 To this end, a variety of technologies for enhancing the permeability of lowpermeability coal seams have been carried out by many researchers, including hydraulic techniques, deep-hole explosive blasting, dense drilling, liquid nitrogen freeze-thaw, fluidized mining, protective-layer mining, and the acidification technique. 10−16 These methods have had some success in increasing the permeability of low-permeability coal seams but have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [12] found that during freezing periods, water in porous media such as rock and concrete tends to form ice or migrate, leading to the redistribution of pore water. Li et al [13][14][15][16] studied the freeze-thaw effect of liquid nitrogen and the pore size, porosity, and permeability of coal rocks; these characteristics were all found to increase with the increase of water saturation. One study analysed the effects of the changes in different conditions on water migration by developing a coupled hydrothermal model for numerical simulation [17].…”
Section: Introductionmentioning
confidence: 99%